Konstrukční výzkum učebnice pro výuku odborného anglického jazyka - Ellederová, Eva (Cizí jazyky a jejich didaktiky: teorie, empirie, praxe, 2022)
Title in English: Design-based Research of an ESP Coursebook This book deals with the concept of design-based research which presents a challenge for English for specific purposes (ESP) teachers to deal with complex curriculum issues in dynamic contexts of teaching practice. The development of learning materials seems to be a fact of life for many ESP teachers. Even though there are many empirically grounded studies for the development of English language learning materials, only a few studies deal with ESP materials development that would provide potential authors with instructions on how to proceed with their design. Design-Based Research of an ESP Coursebook offers a solution to this problem since it describes the systematic implementation, evaluation, and development of an ESP coursebook with the aim of producing design principles and empirically grounded theories. It is believed that the design principles presented in this book should provide a basis for adaptation to other situations, that is, they can help teachers to develop ESP coursebooks tailored for their own courses.